A brief history of philosophy : from Socrates to Derrida - Johnston, Derek (Continuum, 2006)
This title offers a fun, concise and attractive introduction to a fascinating and challenging subject. This is the ideal book for teenagers and students coming to philosophy for the first time, or indeed for anyone who just doesn't know where to start. The book examines 18 key thinkers, from Socrates to Derrida, exploring their ideas in relation to each other and to their historical and cultural contexts. Derek Johnston uses clear and accessible language to present an engaging chronological picture of the key figures, events and ideas that have shaped the history of philosophy. Boxes giving timelines of key events and crisp, clear explanations of key terms feature throughout the book. The book can be easily used as a reference tool or read all the way through for a clear overview of philosophy. Indeed, as the reader's understanding of the nature of philosophy develops, so too does the book's approach to its subject matter, introducing more complex ideas as the chapters progress. Crucially, the book does not try to cover everything - this is a concise and accessible introduction to philosophy for those starting out in this compelling subject. No prior knowledge of philosophy is required to enjoy this incisive, reader-friendly introduction. This is the ideal book for AS/A2 level students or general readers looking for a way into this fascinating, but very often challenging subject.